Do you call these speech errors or language disorder? (2013)
It is often assumed that the apparent errors children make in terms o f omissions or substitutions in an attempt to produce adult speech are generalised. Some even confuse them with speech disorders or errors. However, it has been proved that children are systematic in their production and they follow specific principles and patterns in the process of language acquisition. Literature showed that these processes are not only universal, but hierarchically ordered. Data for this study were obtained from the author's children at different ages, ranging from 1 to 2'A years, and have been used to teach Language Acquisition and Second Language Learning- a final year course in the Department o f Linguistics and African Languages, University o f Ibadan (LIN 472) since 2006/2007 session with positive results. This paper further discussed 11 phonological processes which are involved in the development o f linguistic skills and disagreed with the general assumption and misconception about apparent speech problems in children